A patent review of polyphenol nano-formulations and their commercialization. (February 2022) - Rambaran, Theresa F.
Abstract: Background: The innovative application of nanotechnology to improve the physicochemical properties of polyphenols in the pharmaceutical, nutraceutical, food and cosmetic industries has increased steadily over the last two decades. This proliferation of novel research output and the commercialization of polyphenol nano-formulations has however raised concerns about whether the current state of the regulations governing these products is sufficient. Scope and approach: The use of nanotechnology to prepare state-of-the-art polyphenol nano-formulations was investigated along with their available commercialized forms. Special focus was placed on the types of polyphenols used, the industries in which applications were found, along with the geographical distribution of both patents and commercialized products. The paper also highlights the medical claims of the patented technologies and evaluates current challenges involving their entry into the market. Key findings and conclusions: A large number of nano-polyphenols are being patented and commercialized. A total of 97 nano-polyphenol patents published over the last three years (2019–2021) were found. Approximately 90% of these have potential application in the pharmaceutical or nutraceutical industries. While the medical claims of the patented technologies involving nano-polyphenols are quite diverse, there is no indication that these claims are guided by clinical research. This underscores the significance of firm policies in regulating these products especially given the rate at which they are entering the market. The role nano-polyphenols play in imparting health effects should be supported by sound scientific and clinical data so their safety and efficacy can be validated. This review can impact current regulations and future research. Highlights: Inventions or filed patent applications of polyphenol nano-formulations have increased steadily over the last two decades. Analysis of patented and commercialized nano-polyphenols reveals that most are intended for the nutraceutical industry. Medical claims of nano-polyphenol patents are vast however there is no evidence that they are guided by clinical research. Propagation of nano-polyphenol patents and commercial products warrants firm policies to regulate their safety and efficacy.